GP-OSMOTIC trial protocol: an individually randomised controlled trial to determine the effect of retrospective continuous glucose monitoring (r-CGM) on HbA1c in adults with type 2 diabetes in general practice. Issue 7 (17th July 2018) - Furler, John; O'Neal, David Norman; Speight, Jane; Blackberry, Irene; Manski-Nankervis, Jo-Anne; Thuraisingam, Sharmala; de La Rue, Katie; Ginnivan, Louise; Browne, Jessica Lea; Holmes-Truscott, Elizabeth; Khunti, Kamlesh; Dalziel, Kim; et al.
Abstract : Introduction: Optimal glycaemia can reduce type 2 diabetes (T2D) complications. Observing retrospective continuous glucose monitoring (r-CGM) patterns may prompt therapeutic changes but evidence for r-CGM use in T2D is limited. We describe the protocol for a randomised controlled trial (RCT) examining intermittent r-CGM use (up to 14 days every three months) in T2D in general practice (GP). Methods and analysis: General Practice Optimising Structured MOnitoring To achieve Improved Clinical Outcomes is a two-arm RCT asking 'does intermittent r-CGM in adults with T2D in primary care improve HbA1c?' Primary outcome: Absolute difference in mean HbA1c at 12 months follow-up between intervention and control arms. Secondary outcomes: (a) r-CGM per cent time in target (4–10 mmol/L) range, at baseline and 12 months; (b) diabetes-specific distress (Problem Areas in Diabetes). Eligibility: Aged 18–80 years, T2D for ≥1 year, a (past month) HbA1c>5.5 mmol/mol (0.5%) above their individualised target while prescribed at least two non-insulin hypoglycaemic therapies and/or insulin (therapy stable for the last four months). Our general glycaemic target is 53 mmol/mol (7%) (patients with a history of severe hypoglycaemia or a recorded diagnosis of hypoglycaemia unawareness will have a target of 64 mmol/mol (8%)). Our trial compares r-CGM use and usual care. The r-CGM report summarising daily glucose patterns will be reviewed by GP and patient and inform treatment decisions. Participants in both arms are provided with 1 hour education by a specialist diabetes nurse. The sample (n=150/arm) has 80% power to detect a mean HbA1c difference of 5.5 mmol/mol (0.5%) with an SD of 14.2 (1.3%) and alpha of 0.05 (allowing for 10% clinic and 20% patient attrition). Ethics and dissemination: University of Melbourne Human Ethics Sub-Committee (ID 1647151.1). Dissemination will be in peer-reviewed journals, conferences and a plain-language summary for participants. Trial registration number: >ACTRN12616001372471; Pre-results.